Inducible Rpt3, a Proteasome Component, Knockout in Adult Skeletal Muscle Results in Muscle Atrophy - Kitajima, Yasuo; Suzuki, Naoki; Yoshioka, Kiyoshi; Izumi, Rumiko; Tateyama, Maki; Tashiro, Yoshitaka; Takahashi, Ryosuke; Aoki, Masashi; Ono, Yusuke (Frontiers in Cell and Developmental Biology, 2020)
The ubiquitin–proteasome system has the capacity to degrade polyubiquitinated proteins and plays an important role in many cellular processes. However, the role of Rpt3 depletion has not been investigated in adult muscles in vivo. Herein, we generated skeletal-muscle-specific Rpt3 knockout mice, in which genetic inactivation of Rpt3 could be induced by doxycycline administration. The Rpt3-knockout mice showed a significant reduction by more than 90% in the expression of Rpt3, a crucial proteasomal gene, in adult muscles. Using this model, we found that proteasome dysfunction in adult muscles resulted in muscle wasting and a decrease in the myofiber size. Immunoblotting analysis showed that the amounts of ubiquitinated proteins were markedly higher in muscles of proteasome-deficient mice than in those of the control mice. Analysis of the autophagy pathway in the proteasome-deficient mice showed that the upregulation of LC3II, p62, Atg5, Atg7, and Beclin-1 in protein levels, which supposed to be compensatory proteolysis activation. Our results suggest that the proteasome inhibition in adult muscle severely deteriorates myofiber integrity and results in muscle atrophy.